Las ikastolas en Navarra (siglo XX): búsqueda de un modelo de escuela propio - López Goñi, Irene (Historia de la Educación, 2010)
RESUMEN: En este artículo se aborda la génesis de un fenómeno educativo singular promovido en el seno del pueblo vasco en la lucha por la recuperación de su lengua, el de las ikastolas durante el siglo XX. El límite geográfico es la comunidad de Navarra. Se analizan sus antecedentes antes de la Guerra Civil, el contexto en el que surgen en el período franquista y su proceso de institucionalización. Se ha trabajado con fuentes primarias fundamentalmente. ABSTRACT: In this article, we describe how an educational phenomenon as it is the «ikastola’s» movement in the Basque Country, starts growing in favour of recovering their language during the 20th century. The geographical limit we are going refer to in this article, is the autonomous Community of Navarre. And to analyse this situation we include the preceding details of the experience, before the Spanish Civil War, the context of the development of the experience during Franco’s regime, and the next process of institutionalisation of the ikastola’s experience. The author has worked principally whith primary sources.